2019
DOI: 10.1101/740498
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TPR is required for the nuclear export of mRNAs and lncRNAs from intronless and intron-poor genes

Abstract: While splicing has been shown to enhance nuclear export, it has remained unclear whether mRNAs generated from intronless genes use specific machinery to promote their export. Here we investigate the role of the major nuclear pore basket protein, TPR, in regulating mRNA and lncRNA nuclear export in human cells. By sequencing mRNA from the nucleus and cytosol of control and TPR-depleted cells, we provide evidence that TPR is required for the nuclear export of mRNAs and lncRNAs that are generated from intronless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 84 publications
2
5
0
Order By: Relevance
“…The Ulitsky group also examined how mRNA export was affected by the depletion of TPR, the major component of the nuclear pore basket. In line with what our group previously documented, [ 61 ] they found that TPR was required for the export of intron‐poor mRNAs. These observations suggest that TPR and NXF1 may work together in a pathway that is separate from TREX.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…The Ulitsky group also examined how mRNA export was affected by the depletion of TPR, the major component of the nuclear pore basket. In line with what our group previously documented, [ 61 ] they found that TPR was required for the export of intron‐poor mRNAs. These observations suggest that TPR and NXF1 may work together in a pathway that is separate from TREX.…”
Section: Introductionsupporting
confidence: 90%
“…These junk RNAs are thus retained in the nucleus and targeted for decay. Of course many lncRNAs that function in the cytoplasm, such as NORAD , [ 10,61,62 ] may use GC‐content to acquire export factors as well. It should also be noted that not all GC‐rich regions are created equal.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas it is known that intron-containing genes are surveyed by quality control mechanisms to ensure that unspliced mRNAs are not exported (17), the export mechanisms of intronless genes have not been investigated in great detail. TREX has been suggested to be involved in export of intronless mRNAs in HeLa cells (33), NXF1/TAP pathway in exporting intronless histone H2A mRNA (34) and nuclear pore basket protein TPR in export of intronless transcripts (35). ATXN7L3B was one of the downregulated intronless genes in patients' cells where RNA in situ hybridization showed a reduction in its overall amount but no change in mRNA localization and no evidence for nuclear retention.…”
Section: Discussionmentioning
confidence: 99%
“…Cell Fractionation and RNA Seq Cell fractionation and RNA seq were performed essentially as described in Lee et al (2019), with minor modifications. 1 3 150mm dish of HEK293 Flp-In-TReX cells were depleted of MKRN2 for 5 days.…”
Section: Oligo-dt Experimentsmentioning
confidence: 99%